Jerzy Kmita – interpretacja humanistyczna i społeczno-regulacyjna koncepcja kultury - Bonecki, Mateusz (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
This paper presents two main topics which Jerzy Kmita addresses in his methodological writings. The first one involves the conception of “humanistic interpretation” which Kmita describes as a kind of reasoning and explanation applied within the humanities. The second consists in the so called “socioregulatory definition of culture”, according to which culture is identified with a set of intersubjective beliefs guiding and regulating human actions. Based on both methodological concepts, humanities may be defined as a range of academic disciplines which in the course of humanistic interpretation hypothetically ascribe cultural beliefs to social agents in order to explain their behavior.